Statistical Evaluation of the Major Trends of Globalization - Kovtun, Natalia; Hrazhevska, Nadezhda (Ocena statystyczna podstawowych trendów dotyczących globalizacji, 2010)
On the basis of the research the following important trends of contemporary globalization deployment process can be determined: at the forefront of the growth of globalization, countries are economic factors, the impact of external factors is growing in the dynamics compared to the domestic factors; the role of political factors is significantly reduced, in some groups of countries (first, second, fourth) completely dissipating; characteristic of the last 15 years is a gradual levelling of the role of socio-cultural factors in the development of globalization processes.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 145, s. 59-64
Keywords: trends; contemporary globalization; deployment process